Sequential combined thermal cycling and vibration test and simulation of printed circuit board. (September 2018) - Arabi, F.; Gracia, A.; Delétage, J.-Y.; Frémont, H.
Abstract: Automotive environment generates vibration and temperature fluctuation, which can be damaging for electronic boards. Furthermore, combined temperature and vibration is a type of testing that recreates environments approximating more closely operating environments. In this paper, vibration tests are performed during thermal cycling to investigate the influence of temperature on Printed Circuit Board (PCB) responses. A combined test of temperature and vibration is designed to evaluate the PCB response after each step of one thermal cycle [−40/125] °C. The frequency and displacement can be linked to the strain and strain rate during a board level vibration test. They are obtained from the acceleration during a sine sweep application on a shaker, which is measured using a light weight accelerometer. Experimental results show that temperature significantly affects the PCB responses. Temperature variation leads to striking differences in vibration loading intensity. The PCB first natural frequency shifts from 328 Hz to 313 Hz with temperature increase from 25 °C to 125 °C. A complex PCB is characterized using tension and flexure tests at different temperatures, to extract user input parameter for simulations. An accurate numerical model for sequential combined thermal cycling and vibration simulation is developed and validated using experiments. Thanks to these simulations, the displacement evolution due to combined loading is possible. Highlights: Mechanical characterization of a complex PCB at different temperatures. Design of Experiments of combined thermal cycling and vibration tests. Development and validation of an accurate numerical model for sequential combined thermal cycling and vibration simulation. FEM simulation of the impact of combined thermal and mechanical loading on the PCB reliability. Effects of temperature on the dynamic response of the PCB.